ЛИНГВИСТИЧЕСКАЯ ПРИРОДА РЕЧЕВОЙ ДЕЯТЕЛЬНОСТИ ПЕРСОНАЖА В ХУДОЖЕСТВЕННОМ ТЕКСТЕ - Мамедова, З. Ш. (Eurasian Journal of Philology Science and Education, 2015)
The system approach to a problem of speech activity of the character will help to reveal its communication both with literary vision of the world, and with the general graphic fabric of a work of art. At research of ways of the image of speech activity of the character in the art text an important point is the understanding of unity of its formal and substantial elements from accounts of their purpose and communicativeness.